PENGARUH KELENGKAPAN PENGISIAN FORMULIR INFORMED CONCENT KASUS BEDAH PASIEN RAWAT INAP TERHADAP SNARS EDISI 1 ELEMEN PENILAIAN HPK 5.2 DI RUMAH SAKIT UMUM PINDAD BANDUNG - Sali Setiatin; Yayah Fauziyah (INFOKES (Informasi Kesehatan), 2019)
The reseach aimed to know The Influence Of Completeness Form Informed Consent Surgical Cases Of Inpatients To SNARS Edition 1 Element Of Assesment HPK 5.2 At Rumah Sakit Umum Pindad Bandung. The research method used quantitative research with descriptive approach and data processing using SPSS version 16 program. Data collecting dissemination of the observation, interview, documentation, and review of the literature. Sampling teqnique used purposive sampling with a sample of 235 form surgical cases of inpatients. From the result of an intensive writers could formulate the subject matter that 1) it was still found filling informed consent Surgical Cases Of Inpatients from that’s not completed, there was 69 or 29% informed consent form filing uncompleteness 2) recording form informed consent of inpatient surgical cases in a hurry 3) lack of implementation in filling out informed consent form of inpatient surgical cases 4) lack of accuracy in filling out informed consent forms of inpatient surgical cases. The suggestion were given by :1) Giving punishment if informed consent form of inpatient surgical cases was reporting uncompletely 2) Increasing the complete informed consent form of inpatient surgical cases 3) Holding monitoring or evaluation by the hospital, 2) Coordination directly with the physician about the incompleteness from surgical cases of inpatients.